1992 ネン アイスランド キョウヤクテン カンソク ト ゲンジョウ - 加藤, 賢一; カトウ, ケンイチ; 小野, 高幸; オノ, タカユキ; 國武, 学; クニタケ, マナブ; 佐藤, 夏雄; サトウ, ナツオ; Saemundsson, Thorestein; Kato, Ken-ichi; Ono, Takayuki; Kunitake, Manabu; et al. (1993)
P(論文) 本報告では, 1992年に著者らがアイスランドで行った共役点観測と定常観測のメンテナンスについて記述する。その共役点観測はHusafellを中心として, 全天SIT TVカメラによるオーロラ光学観測, multi channel scanning photometerによるオーロラ輝線強度観測そしてGPSやNNSSを用いたTECmeterによる電離層観測を同時に行った。定常観測のメンテナンスは, VLFアンテナの建て替え, induction磁力計の交換やfluxgate磁力計の設置場所の移動等を主に行った。アイスランドにおける共役点観測は約10年がたち, 観測機器の老朽化が顕著に現れてきている。これらの観測機器の故障等の原因の推測とそれら定常観測システムの現状と問題点について考えてみた。 The present paper describes the observation system and the maintenance work which the authors performed during the conjugate aurora observation period, from September 1 to October 5,1992. The observation program consisted of observation of visible auroras with an all-sky SIT TV camera, aurora emission (670.5nm and 844.6nm) intensity measurements with a multi channel scanning photometer and ionosphere electron density measurement with a TECmeter that used radio waves transmitted from GPS and NNSS satellites. For the present observation program in 1993,new observation systems have been additionaly facilliated with the all-sky TV, scanning photometer and TECmeter. Maintenance work was performed on the continuous observation system. The main work was to rebuild a VLF antenna, to change induction magnetometer sensors and to remove a fluxgate magnetometer sensor. It is noted that continuous observation systems present several problems including superanuation and difficulty in obtaining spare parts. departmental bulletin paper